2020
DOI: 10.1017/aae.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Behavioral Change Using Text Messages: A Case Study of Blackberry Farmers in Ecuador

Abstract: This study measures the effect of text message receipt on behavioral change by Ecuadorean blackberry farmers. We examine whether text messages affect knowledge about specific technologies or serve as reminders to farmers to employ practices as part of their crop management strategy. Drawing from well-known theories of behavioral change, we identify pathways relevant to technology adoption. We then describe results from a randomized experiment and measure the impact of the intervention through these pathways. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…The results reveal that the marginal effect of the smartphone use variable is positive and statistically significant, suggesting that farmers who use smartphones to acquire agricultural information are 23.9% more likely to adopt DTWVs. The finding is well in line with the results of previous studies (Carrión-Yaguana et al, 2020;Kiiza & Pederson, 2012). For example, Kiiza and Pederson (2012) found that information provided by mobile phones increases the probability of improved seed adoption in Uganda.…”
Section: Direct Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…The results reveal that the marginal effect of the smartphone use variable is positive and statistically significant, suggesting that farmers who use smartphones to acquire agricultural information are 23.9% more likely to adopt DTWVs. The finding is well in line with the results of previous studies (Carrión-Yaguana et al, 2020;Kiiza & Pederson, 2012). For example, Kiiza and Pederson (2012) found that information provided by mobile phones increases the probability of improved seed adoption in Uganda.…”
Section: Direct Effectssupporting
confidence: 90%
“…Smartphone use provides farmers an efficient way to access information on drought and modern crop varieties, which enables them to learn more knowledge about DTWVs. Carrión-Yaguana et al (2020) noted that access to information via the Internet positively impacts the blackberry management strategy of adoption in Ecuador. We, therefore, expect that smartphone-based information acquisitors are more likely to adopt DTWVs.…”
Section: Key Variable Measurementsmentioning
confidence: 99%
“…Based on a literature review, we propose two potential pathways through which the adoption of smartphone‐based agricultural extension services influences farm incomes. Instead of a blanket of information, smartphone‐based agricultural extension services provide site‐specific recommendations to farmers (Arouna et al, 2021; Oyinbo et al, 2022), which helps them to identify inputs and technological information more accurately (Carrión‐Yaguana et al, 2020; Nakasone et al, 2014). On the one hand, this will further lead to better farm performance, such as increased crop yield and higher productivity (Adolwa et al, 2019; Aker & Ksoll, 2016), resulting in improved farm income from fields using the soil testing formula fertilizer (hereinafter abbreviated to “farm income from STFF fields”) and total farm income (Ma, Grafton, et al, 2020; Manda et al, 2016).…”
Section: Conceptual Framework and Empirical Strategymentioning
confidence: 99%